Analysis of interactions with the mammalian deubiquitinating enzyme, USP4 - Twomey, Erin (University of Ottawa (Canada), 2003)
We have previously reported the cloning of the murine USP4 (previously Unp) and human USP4 (previously Unph) genes. These genes encode ubiquitin specific proteases capable of cleaving ubiquitin tags from synthetic substrates in vitro. However, the natural substrates of this deubiquitinating enzyme are not known. It has been shown that USP4-overexpressing NIH3T3 cells consistently produce tumors in nude mice experiments and USP4 has been implicated in specific types of human lung tumors such as small cell and adenocarcinomas. Unlike some other deubiquitinating enzymes, USP4 does not have an overall affect on cellular ubiquitination. Therefore, it is thought that USP4 has only one or a few substrates and that it may be functioning by stabilizing a protein by editing its ubiquitin degradation signal. As a first step in attempting to identify USP4's substrate(s), we have been looking for proteins that may interact with USP4. We have done this using an in vitro pull down system and mass spectrometry analysis. The translational elongation factor, EF1A, was identified by mass spectrometry and this interaction was confirmed in vivo using immunoprecipitations and immunofluorescence.
Keywords: Chemistry, Biochemistry.